High-molecular-mass hyaluronan mediates the cancer resistance of the naked mole rat - Tian, Xiao; Azpurua, Jorge; Hine, Christopher; Vaidya, Amita; Myakishev-Rempel, Max; Ablaeva, Julia; Mao, Zhiyong; Nevo, Eviatar; Gorbunova, Vera; Seluanov, Andrei (Nature (London), 2013)
Naked mole rats seem almost entirely protected from developing cancer, and this can now, at least in part, be explained by the production of a unique high-molecular-mass form of hyaluronan, a component of the extracellular matrix; together with an increased sensitivity of naked mole-rat cells to hyaluronan signalling, this form protects its cells from oncogenic transformation. The giant molecule that keeps naked mole rat cancer-free Naked mole rats are remarkable in combining extreme longevity with virtually complete resistance to cancer. Now a novel glycosaminoglycan variant that may have evolved to provide the creatures with the tough, flexible skin needed for a subterranean lifestyle has been identified as a key contributor to their cancer resistance. Hyaluronan, or hyaluronic acid, is a ubiquitous component of the extracellular matrix. Xiao Tian et al . observed that the culture media of naked mole-rat fibroblasts becomes viscous owing to the accumulation of a thick 'gooey' substance and identified it as a high-molecular-mass hyaluronan (HMM-HA), more than five times larger than mouse and human equivalents. It accumulates in naked mole-rat tissues owing to low hyaluronidase activity and a unique form of hyaluronan synthase 2. HMM-HA acts through the CD44 receptor and removal of HMM-HA makes naked mole-rat cells more susceptible to transformation. This unusual model of cancer protection suggests potential new avenues of research into anticancer and life-extension strategies. The naked mole rat ( Heterocephalus glaber ) displays exceptional longevity, with a maximum lifespan exceeding 30 years 1 , 2 , 3 . This is the longest reported lifespan for a rodent species and is especially striking considering the small body mass of the naked mole rat. In comparison, a similarly sized house mouse has a maximum lifespan of 4 years 4 , 5 . In addition to their longevity, naked mole rats show an unusual resistance to cancer. Multi-year observations of large naked mole-rat colonies did not detect a single incidence of cancer 2 , 6 . Here we identify a mechanism responsible for the naked mole rat’s cancer resistance. We found that naked mole-rat fibroblasts secrete extremely high-molecular-mass hyaluronan (HA), which is over five times larger than human or mouse HA. This high-molecular-mass HA accumulates abundantly in naked mole-rat tissues owing to the decreased activity of HA-degrading enzymes and a unique sequence of hyaluronan synthase 2 ( HAS2 ). Furthermore, the naked mole-rat cells are more sensitive to HA signalling, as they have a higher affinity to HA compared with mouse or human cells. Perturbation of the signalling pathways sufficient for malignant transformation of mouse fibroblasts fails to transform naked mole-rat cells. However, once high-molecular-mass HA is removed by either knocking down HAS2 or overexpressing the HA-degrading enzyme, HYAL2, naked mole-rat cells become susceptible to malignant transformation and readily form tumours in mice. We speculate that naked mole rats have evolved a higher concentration of HA in the skin to provide skin elasticity needed for life in underground tunnels. This trait may have then been co-opted to provide cancer resistance and longevity to this species.